Descrição de documentos na internet e em eBooks - Honorato, Mauro Jacob (2011)
The Internet and ebooks are replacing traditional publishing houses. Encyclopedias, for instance, are published mainly in the Internet, since this media allows fast update, cooperation and corrections. Electronic readers decreased the cost of publishing books, and spare natural resources (wood for papers, for instance) needed for printting documents Since long, publishing technology have advanced two domain specific languages for describing documents: LATEX and XML. In recent years, XML became the choice tool for the Internet, text processing, and electronic edition of books. Therefore, this dissertation will offer tools for producing XML for www pages, and also for electronic publishing. The Scheme programming language is a dialect of LISP well suited for text processing, since it has a good representation for structured text: Nested lists. Thus the author of this work will describe how to use Scheme for creating dynamic pages based on their XML description. If global communication is to become feasible, we must adapt the technological advances that people who work with Artificial Intelligence made in the fields of knowledge representation, context capture, domain specific languages, reflexivity, and natural language processing. In general, AI technologies are expressed in languages of the LISP family, since they are homoiconic, i.e., their primary representation of programs is also a data structure in a primitive type of LISP. This makes metaprogramming easier than in a language without this property. This paper will show how to use metaprogramming and closures for skimming through a restricted domain text in order to grasp its syntactic structure and meaning. Once the software system obtains the general features of a text, it can process it to generate books that can be installed in dedicated reading devices; it can also generate dictionaries and digests to easy the process of reading. Finally this work will address the problem of publishing ebooks, after specifying their structure in XML.